Attitudes towards scientific research in university students: Analysis in two national universities of Lima - de la Cruz Valdiviano, Carlos (2013)
The attitudes toward the scientific investigation were analyzed in students of two National Universities of Lima: National University Federico Villarreal (Universidad Nacional Federico Villarreal, UNFV) and The National University of Engineering (Universidad nacional de ingeniería, UNI). For such purpose, the Scale of Attitudes toward the scientific investigation of Portocarrero y De La Cruz (2006) was used, instrument psychometrically evaluated to determine its validity and reliability. Subsequently, it was administered to two groups of university students (Psychology of the UNFV = 115 and Civil Engineering of the UNI = 140) who were selected in a simple random sampling. The results showed that there are not significant differences (p<0.01) regarding the UNFV students, who showed a more positive attitude in the subscale of scientific training compared to UNI students. While there are similar mean scores in the sub-scales trainer teachers and attitude toward scientific interest (proactivity). Moreover, this similarity is seen in the total score. On the other hand, for origin and religion there are not significant in differences. Finally, attitudes towards trainer teachers and the scientific training given to students are the best predictors of interest for research.